Creating opportunities to end hunger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Despite years of international effort, scientific advance and the dedication of man) men and women worldwide between 500 million and on' billion of the world's poorest inhabitants still lack the opportunity to meet their most basic need to be...